THE EFFECT OF USING THE KETO DIET AND STATION TRAINING ON SOME MOTOR ABILITIES IN OBESE PEOPLE - Asaad Jassim Shanan; Dr Fairouz AZAIEZ (Proximus Journal Publishing, 2024)
The aim of the research was to determine the effect of keto diet and station training on some motor variables in obese individuals. In order to determine the effect of the keto diet and station training on some motor abilities and obese people, the research population was defined as obese people aged (20-25 years). 25) years old obese people who are present in the fitness halls, and the research sample was selected from obese people (8) individuals if a one-group experimental design with pre and post-test was used, and the sample was selected by the random method from obese people and (2) individuals were taken to conduct the exploratory experiment on them from within the same experimental group and the percentage of the sample was (100%) of those registered in the fitness hall
Keywords: experimental; within; percentage